SOSIOLOGI PENDIDIKAN SEBAGAI ILMU PENGETAHUAN - Andi Nabilla Zakiyah; Wira Sapitri; Trisna Liza (DE FACTO : Journal Of International Multidisciplinary Science, 2024)
In the Indonesian context, the sociology of education is becoming increasingly relevantbecause Indonesia has a complex and diverse education system, and there are still manychallenges that must be faced in improving the quality of education. Educational issues covervarious aspects related to education, such as access to education, quality of education, andeducational disparities. In this study, literature studies were used to find sources of informationto find scientific research based on relevant literature on the topic in question and theory. Thistype of library research is related to library data collection, obtaining information from variouslibraries, one of which is scientific journals. The implications of the sociology of education i neducation are that education must consider social factors such as social class, gender, race, andreligion in designing educational programs that are more inclusive and effective.